To find an expression that has the same sum as \(-15 + 6\), we first calculate the original expression:
\(-15 + 6 = -9\).
Now, let's evaluate the given options to see which one also equals \(-9\):
-
\(-6 + (-15)\): \(-6 - 15 = -21\), which is not \(-9\).
-
\(15 + 6\): \(15 + 6 = 21\), which is not \(-9\).
-
\(15 + (-6)\): \(15 - 6 = 9\), which is not \(-9\).
-
\(6 + (-15)\): \(6 - 15 = -9\), which matches our original calculation.
The correct expression that has the same sum as \(-15 + 6\) is:
\(6 + (-15)\).